2008
DOI: 10.1016/j.visres.2007.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceptual learning on primary visual cortex activity in humans

Abstract: Psychophysical and neuroimaging studies suggest that perceptual learning may affect activity in primary visual cortex (V1). Yet, it remains unclear whether such changes involve intrinsic V1 plasticity or feedback from later processing stages. Here we recorded high-density electro-encephalography in 24 volunteers, 24-h after training on a visual texture discrimination task in the upper or lower visual-field. Post-training improvement in upper visual-field was associated with changes in early visual responses, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
133
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 39 publications
34
133
6
Order By: Relevance
“…Importantly, regression analysis revealed variability in modulation indices across individuals was correlated with performance variability and thus suggests that the learning effect is related to physiological changes. The current findings linking practice-related WM improvement with decreased interference processing are in line with reports of decreases in visual cortical activity with learning in previous ERP (Pourtois et al 2008), fMRI (Milham et al 2003;Mukai et al 2007), and PET (Schiltz et al 1999) studies.…”
Section: Influence Of Practice On Interference Processing and Wmsupporting
confidence: 91%
“…Importantly, regression analysis revealed variability in modulation indices across individuals was correlated with performance variability and thus suggests that the learning effect is related to physiological changes. The current findings linking practice-related WM improvement with decreased interference processing are in line with reports of decreases in visual cortical activity with learning in previous ERP (Pourtois et al 2008), fMRI (Milham et al 2003;Mukai et al 2007), and PET (Schiltz et al 1999) studies.…”
Section: Influence Of Practice On Interference Processing and Wmsupporting
confidence: 91%
“…in (Pourtois et al, 2008;Rauss et al, 2009). The peripheral textures were presented with a temporal jitter with respect to the offset of the central stimuli, thus never overlapping in time with them, and they were to be ignored by the participants.…”
Section: Stimuli and Taskmentioning
confidence: 97%
“…The C1 has for a long time been described as being resistant to modulatory effects exerted by distant fronto-parietal attention control regions onto lower tier visual cortex (Clark and Hillyard, 1996;Handy et al, 2001;Martinez et al, 1999). More recently, systematic C1 amplitude changes have been reported with top-down cognitive manipulations (see Rauss et al, 2011a for a recent review), including perceptual learning and expertise (Bao et al, 2010;Jin et al, 2010;Pourtois et al, 2008), emotional valence (Eldar et al, 2010;Halgren et al, 2000;Pourtois et al, 2004;West et al, 2011), and featurebased or spatial attention (Karns and Knight, 2009;Kelly et al, 2008;Proverbio et al, 2010;Zani and Proverbio, 2009). With regards to attention, not only increases of the C1 to attended visual stimuli were shown, but also substantial reductions of this same early visual component to unattended or task-irrelevant stimuli were evidenced, suggesting flexible and adaptive gain control mechanisms exerted by putative fronto-parietal networks onto lower tier visual cortex, 2009, 2011b) and emotion control (Stolarova er al., 2006) by themselves yield amplitude modulations of the C1 component during visual perception, we hypothesized a possible combined effect of the two factors influencing this early visual evoked component.…”
Section: Permeability Of Human V1 To Cognitive Factorsmentioning
confidence: 99%
“…1a). These unpredictable and uninformative peripheral stimuli were previously associated with the generation of a reliable C1 component, with its main generators source-localized in V1 (Pourtois et al, 2008;Rauss et al, 2009). In the other 50% of the trials, no peripheral stimulus was shown in periphery during the ISI, but in order to maintain the exact same temporal structure for all trials a black dummy was presented for the same duration (invisible to the participants).…”
Section: Stimuli and Taskmentioning
confidence: 97%